Exploring the Role of Psychology in Strategic Human Resource Management: A Qualitative Perspective with Literature Review - Paroli, P. (Golden Ratio of Human Resource Management, 2025)
This qualitative study explores the integration of psychological principles into Strategic Human Resource Management (SHRM) practices and its implications for organizational performance. The research aims to elucidate the role of psychology in shaping HR strategies, particularly focusing on employee motivation, satisfaction, and engagement. A comprehensive literature review was conducted to synthesize existing research on psychological theories such as Maslow's hierarchy of needs, Herzberg's two-factor theory, and social identity theory in the context of SHRM. The study also investigates the impact of leadership paradigms, including transformational and authentic leadership, on organizational culture and effectiveness. Findings suggest that integrating psychological insights into HR practices enhances employee well-being, resilience, and organizational performance. Transformational and authentic leadership principles contribute to creating a positive work environment characterized by collaboration, innovation, and employee empowerment. The research underscores the importance of interdisciplinary collaboration between psychology and HRM in optimizing human capital management efforts.